2017
DOI: 10.1016/j.jelechem.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The voltammetry of surfaces vicinal to Pt{110}: Structural complexity simplified by CO cooling

Abstract: By flame-annealing and cooling a series of Pt n{110} × {111} and Pt n{110} × {100} single crystal electrodes in a CO ambient, new insights into the nature of the electrosorption processes associated with Pt{110} voltammetry in aqueous acidic media are elucidated. For Pt n{110} × {111} electrodes, a systematic change in the intensities of so-called hydrogen underpotential (Hupd) and oxide adsorption voltammetric peaks (for two dimensionally ordered (1 × 1) terraces and linear {111} × {111}step sites) point to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 47 publications
7
35
0
Order By: Relevance
“…For the Pt(111) and Pt(100), this procedure leads to the formation of a well-ordered surface with the nominal orientation [20,21]. Due to the reconstruction phenomena undergone by the Pt(110) surfaces, which is strongly affected by the treatment, the surface presented here corresponds to the (1 × 2) or (1 × 1)/(1 × 2) structure with major (1 × 2) contribution [22,23]. Thus, the observed behavior should correspond with that expected for the (1 × 2) surface, although contributions from the (1 × 1) cannot be discarded.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the Pt(111) and Pt(100), this procedure leads to the formation of a well-ordered surface with the nominal orientation [20,21]. Due to the reconstruction phenomena undergone by the Pt(110) surfaces, which is strongly affected by the treatment, the surface presented here corresponds to the (1 × 2) or (1 × 1)/(1 × 2) structure with major (1 × 2) contribution [22,23]. Thus, the observed behavior should correspond with that expected for the (1 × 2) surface, although contributions from the (1 × 1) cannot be discarded.…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that the voltammograms for this surface are very sensitive to the actual structure of the electrode, likely related to the fraction of the surface having the (1 × 2) reconstruction. This ratio depends, in turn, on the annealing conditions [23], so that the measured currents for the methanol oxidation reaction for this electrode show large variability. For the Pt(110) electrode, the voltammogram for the oxidation of methanol shows a wave with a complex shape in the positive scan, whose onset is located at ca.…”
Section: Pt(100) and Pt(110) Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…As with many studies involving Pt{110} single crystals (including reference [11]), preparation of the well-defined surface was achieved using Clavilier's flame-annealing method [24] with subsequent cooling of the crystal in a hydrogen atmosphere [25]. In two recent publications, it has been shown that such treatment will lead to a Pt{110} surface that is not optimal so far as long range order is concerned [26,27]. Rather, in order to generate the largest, defect-free Pt{110}-(1x1) planes, it is necessary to cool a flame-annealed Pt{110} electrode in a stream of CO in order to preclude the formation of Pt{110}-(1x2) reconstructed domains which may subsequently result in surface disorder associated with the lifting of the (1x2) phase to the (1x1) phase [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…In two recent publications, it has been shown that such treatment will lead to a Pt{110} surface that is not optimal so far as long range order is concerned [26,27]. Rather, in order to generate the largest, defect-free Pt{110}-(1x1) planes, it is necessary to cool a flame-annealed Pt{110} electrode in a stream of CO in order to preclude the formation of Pt{110}-(1x2) reconstructed domains which may subsequently result in surface disorder associated with the lifting of the (1x2) phase to the (1x1) phase [26][27][28][29][30][31]. Because the surface density of platinum atoms in the (1x2) phase is 50% higher than for the (1x1) phase, lifting of the surface reconstruction will result in an excess of Pt{110}-(1x1) islands on-top of the underlying, flat nominal Pt{110}-(1x1) plane [32].…”
Section: Introductionmentioning
confidence: 99%